Vascular Endothelial Growth Factor Is Associated with the Morphologic and Functional Parameters in Patients with Hypertrophic Cardiomyopathy. (30th December 2015) - Pudil, Radek; Vasatova, Martina; Fucikova, Alena; Rehulkova, Helena; Rehulka, Pavel; Palicka, Vladimir; Stulik, Jiri
Abstract : Background . Hypertrophic cardiomyopathy (HCM) is mostly autosomal dominant disease of the myocardium, which is characterized by myocardial hypertrophy. Vascular endothelial growth factor (VEGF) is involved in myocyte function, growth, and survival. The aim of study was to analyze the clinical significance of VEGF in structural and functional changes in patient with HCM. Methods . In a group of 21 patients with nonobstructive HCM, we assessed serum VEGF and analyzed its association with morphological and functional parameters. Compared to healthy controls, serum VEGF was increased: 199 (IQR: 120.4–260.8) ng/L versus 20 (IQR: 14.8–37.7) ng/L, P < 0.001 . VEGF levels were associated with left atrium diameter (r = 0.51, P = 0.01 ), left ventricle ejection fraction (r = - 0.56, P = 0.01 ), fractional shortening (r = - 0.54, P = 0.02 ), left ventricular mass (r = 0.61, P = 0.03 ), LV mass index (r = 0.46, P = 0.04 ), vena cava inferior diameter (r = 0.65, P = 0.01 ), and peak gradient of tricuspid regurgitation (r = 0.46, P = 0.03 ). Conclusions . Increased VEGF level is associated with structural and functional parameters in patients with HCM and serves as a potential tool for diagnostic process of these patients.